Equine arteritis virus-infected cells contain six polyadenylated virus-specific RNAs - Van Berlo, Mario F. (Virology, 1982)
The kinetics of equine arteritis virus growth and virus-specific RNA synthesis at 40° were determined in BHK-21 cells. Maximum titers of infectious virus (∼10(7) PFU/ml) were observed at 12 hr p.i., while incorporation of [(3)H]uridine into virus-specific RNA became detectable at 4 hr p.i. and increased to reach a maximum rate at 8 hr p.i. This RNA was labeled between 2.5 and 7 hr p.i. and isolated from infected cells. About 44% bound to oligo(dT)-cellulose; this material was denatured using glyoxal and dimethyl sulfoxide and analyzed by electrophoresis in a 1% agarose-urea gel. Six virus-specific RNA species were found having the following molecular weights: 4.3 × 10(6) (RNA1), 1.3 × 10(6) (RNA2), 0.9 × 10(6) (RNA3), 0.7 × 10(6) (RNA4), 0.3 × 10(6) (RNA5), and 0.2 × 10(6) (RNA6). RNA1 comigrated with the viral genome. Artifacts caused by defective interfering particles or breakdown of RNA were excluded. Subsequently, the target sizes of the templates for the synthesis of the genome-sized RNA and the five subgenomic RNAs were determined by uv transcription mapping. Infected cells were irradiated at 6.5 hr p.i. The effect o of reasing uv doses on the RNA synthesis was determined by quantitation of the individual RNAs after separation by agarose gel electrophoresis. The uv target sizes calculated for the templates for RNAs 2–5 were very close to the physical size of RNA1. The target size of the template of RNA6 was smaller (2.8 × 106 daltons), although much greater than its physical size. The data are consistent with a model in which the individual RNAs are derived from a larger precursor RNA molecule. The consequences of these findings for the taxonomy of Togaviridae are discussed.